2018
DOI: 10.14419/ijans.v7i1.11814
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ KAP related to research conduct and utilization: EBNP “are we ready yet.

Abstract: Background: Nurses make a positive difference every day and continue to shape the future of healthcare through planning, implementation and dissemination of quality research studies. The practice of evidence-based nursing is determined by the nurse’s clinical experience as well as clinically relevant research knowledge, willingness to apply research to practice, and the skills to do so. No previous studies had been conducted to assess the conduct and utilization of nursing research and EBP in the Easte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
1
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
(18 reference statements)
2
1
2
Order By: Relevance
“…From table 4, reasons identified to influence utilization of research findings include: lack of support and approval from organization, lack of awareness of the research finding, Poor support/ cooperation from co-health worker, insufficient time on the job to read research findings, lack of knowledge of benefit of research, lack of support from colleagues, insufficient time on the job to implement new ideas, minimal authority on part of nurses to change procedure, research report not being published fast enough, research report not readily available, lack of research committee, inadequate facilities, isolation from knowledgeable colleague. The outcome of this research goes in line with researches of various authors that 66 Article DOI: 10.52589/AJHNM-JZN8F7OQ DOI URL: https://doi.org/10.52589/AJHNM-JZN8F7OQ www.abjournals.org revealed that organization influence, lack of research skill and development, lack of interest to read research papers, lack of authority, lack of time, insufficient understanding of research process and findings, lack of resources, and inadequate organizational support ( Abouelfettoh & Ateeq, 2018;Adejumo & Guobadia, 2013;Bahadori et al, 2016a& Tan et al, 2012.…”
Section: Discussion Of Findingssupporting
confidence: 87%
See 1 more Smart Citation
“…From table 4, reasons identified to influence utilization of research findings include: lack of support and approval from organization, lack of awareness of the research finding, Poor support/ cooperation from co-health worker, insufficient time on the job to read research findings, lack of knowledge of benefit of research, lack of support from colleagues, insufficient time on the job to implement new ideas, minimal authority on part of nurses to change procedure, research report not being published fast enough, research report not readily available, lack of research committee, inadequate facilities, isolation from knowledgeable colleague. The outcome of this research goes in line with researches of various authors that 66 Article DOI: 10.52589/AJHNM-JZN8F7OQ DOI URL: https://doi.org/10.52589/AJHNM-JZN8F7OQ www.abjournals.org revealed that organization influence, lack of research skill and development, lack of interest to read research papers, lack of authority, lack of time, insufficient understanding of research process and findings, lack of resources, and inadequate organizational support ( Abouelfettoh & Ateeq, 2018;Adejumo & Guobadia, 2013;Bahadori et al, 2016a& Tan et al, 2012.…”
Section: Discussion Of Findingssupporting
confidence: 87%
“…Also, the outcome of this study corroborate with the studies of (Abouelfettoh & Ateeq, 2018;Heydari & Zeydi, 2014;Kajermo et al, 1998;Kousar et al,2017;Tuppal et al, 2019;Wang et al, 2013& Zhou et al, 2015 that identified organizational policy, lack of time on the job to read research findings ,lack of authority to change patient procedure of care and administration not allowing implementation of research findings, lack of facilities ,perceived little benefit, respondents feel benefit of changing research will be minimal and not seeing the value of research for practice. Also, Oluwatosin (2014) considered time related issues as the leading barrier.…”
Section: Discussion Of Findingssupporting
confidence: 84%
“…Regarding research participation and knowledge of the study participants, only 18.6 % and 13.9% of paramedical team and administrative teams respectively had a previous participation in a scientific research which is considered to be low participation. This was in contrast with Abouelfettoh and Al Ateeq's study where 31.2% (206/ 660) of paramedical nurses had a previous participation on a research [10]. This difference may be due to the fact that in current study paramedical team included technicians who were not interested in doing medical Positive attitude answers are in italics, and the most frequent answers are in boldface research and nurses who were not yet involved in medical research and had no sufficient opportunities for involving in research.…”
Section: Discussioncontrasting
confidence: 66%
“…In the present study, 94.3% and 85.3% of the paramedical team and administrative teams respectively knew that scientific research is important in helping to serve patients which was a high level of knowledge in comparative to Abouelfettoh and Al Ateeq's study where nurses' knowledge about research were moderate [10]. This indicates that the NLI paramedical and administrative teams need only opportunity to participate in a research with their high knowledge about research importance.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation